MODIFIED BIOT-GASSMANN THEORY FOR CALCULATING ELASTIC VELOCITIES FOR UNCONSOLIDATED AND CONSOLIDATED SEDIMENTS - Lee M.W. (My University, 2002)
The classical Biot-Gassmann theory (BGT) generally overestimates shear-wave velocities of water-saturated sediments. To overcome this problem, a new theory is developed based on BGT and on the velocity ratio as a function of G(1-φ)n, where φ is porosity and n and G are constants. Based on laboratory data measured at ultrasonic frequencies, parameters for the new formulation are derived. This new theory is extended to include the effect of differential pressure and consolidation on the velocity ratio by making n a function of differential pressure and the rate of porosity reduction with respect to differential pressure. A scale G is introduced to compensate for discrepancies between measured and predicted velocities, mainly caused by the presence of clay in the matrix. As differential pressure increases and the rate of porosity reduction with respect to differential pressure decreases, the exponent n decreases and elastic velocities increase. Because velocity dispersion is not considered, this new formula is optimum for analyzing velocities measured at ultrasonic frequencies or for sediments having low dispersion characteristics such as clean sandstone with high permeability and lack of grain-scale local flow. The new formula is applied to predict velocities from porosity or from porosity and P-wave velocity and is in good agreement with laboratory and well log data.